Uterine Arteriovenous MalformationA Rare Cause of Abnormal Uterine Bleeding - Begum, Shamsun Nahar; Paul, Shroddha Nivedita; Paul, Fonindra Nath; Jahan, Muna Shalima; Akhter, Parul (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Uterine arteriovenous malformation (AVM) is a rare condition with fewer than 100 cases reported in the literature1. Despite being rare, it is a life threatening condition. In most cases, it is diagnosed during a severe and acute hemorrhagic event. It has a diverse symptomatology. Clinical presentation varies from no symptom to various degree of menorrhagia with massive life threatening vaginal bleeding. Clinical suspicion is essential for a prompt diagnosis and treatment. This case report describes a 24year old woman who presented with recurrent episodes of severe vaginal bleeding for the last 3 years. Initial episode was after a curettege for incomplete abortion 3years back. Trans-abdominal and transvaginal Doppler ultrasound of the pelvis showed presence of numerous tortuous and engorged vessels throughout the myometrium and both adnexal regions. Bilateral uterine and ovarian artery ligation was performed with significant improvement of patients symptom. Bangladesh J Ob et Gynaecol, 2014; Vol. 29(1) : 49-53